2020
DOI: 10.1002/app.49922
|View full text |Cite
|
Sign up to set email alerts
|

CR composites with improved processing safety crosslinked via Heck's reaction

Abstract: The aim of this study was to optimize the composition of the chloroprene rubber (CR) composites crosslinked via the Heck-type reaction to ensure their safe processing at elevated temperature. The developed curing system consisting of iron (III) acetylacetonate (Fe(acac)) and triethanolamine (TEOA) demonstrates high activity and more eco-friendly composition in comparison with metal oxide system, commercially used for CR crosslinking. However, the high activity of Fe(acac)/TEOA system results in a short scorch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The Heck reaction of halogenated aromatics with olefins is among the most direct effective methods for forming C-C bonds and has been extensively applied for the synthesis of drugs and intermediates, natural products, and functional materials. [1][2][3][4] Since the discovery of the Heck reaction, reaction selectivity, catalyst types, and catalytic mechanisms have been intensively studied. [5][6][7] Among the investigated catalysts, traditional homogeneous palladium catalysts show excellent catalytic activity but also have some limitations such as air-sensitivity, poor recyclability and reusability, and cumbersome post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The Heck reaction of halogenated aromatics with olefins is among the most direct effective methods for forming C-C bonds and has been extensively applied for the synthesis of drugs and intermediates, natural products, and functional materials. [1][2][3][4] Since the discovery of the Heck reaction, reaction selectivity, catalyst types, and catalytic mechanisms have been intensively studied. [5][6][7] Among the investigated catalysts, traditional homogeneous palladium catalysts show excellent catalytic activity but also have some limitations such as air-sensitivity, poor recyclability and reusability, and cumbersome post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [ 25 , 26 , 27 , 28 ], we reported the activity of metal acetylacetonates with different transition metals in the presence of triethanolamine (TEOA) as curing agents for CR. The crosslinking of CR with the proposed curing systems was proven to proceed in accordance with the mechanism of Heck reaction [ 26 ].…”
Section: Introductionmentioning
confidence: 99%